Paracanthocobitis hijumensis, a new species of zipper loach from the Arunachal Himalaya, northeastern India (Cypriniformes: Nemacheilidae) - Rime, Gepi; Tamang, Lakpa; Das, Debangshu Narayan (Zootaxa, 2022)
Paracanthocobitis hijumensis, new species, is described from the Hijum River, a tributary of the upper Brahmaputra River in Arunachal Pradesh, India. Paracanthocobitis hijumensis is distinguished from all five species of the P. zonalternans species complex, viz., P. zonalternans, P. nigrolineata, P. marmorata, P. triangula, and P. phuketensis in having a larger body size (46.5– 65.6 mm SL vs. < 45 mm SL), and a complete (vs. an incomplete) lateral line terminating at the end of caudal peduncle (vs. at or just beyond the dorsal-fin insertion); and from the four species of the P. mandalayensis species complex, P. canicula, P. maekhlongensis, P. mandalayensis and P. pictilis in having a subortibal flap (vs. suborbital groove) in males, and in having fewer dorsal-fin branched rays (9½–10½ vs. 10½–13½), and longer head (23.8–26.0% SL vs. 18.0–20.2). Paracanthocobitis hijumensis, a member of the P. botia complex, differs from the other nine species of this complex by the following combination of characters: presence of an axillary pelvic lobe, greater predorsal distance 47.9–51.8% SL, greater prepelvic distance 52.3–58.8% SL, longer head 23.8–26.0% SL, deeper body 18.4–23.1% SL, smaller eye 14.2–22.5% SL, and fewer branched rays on the dorsal-fin 9½ (12)–10½ (1).